2019
DOI: 10.5430/afr.v8n2p86
|View full text |Cite
|
Sign up to set email alerts
|

Fintech Adoption Choices of Small Businesses: A Technology Organization Environment (TOE) Framework study

Abstract: Financial technology or “FinTech” is an amalgam of the use of technology for financial transactions and processes. Fintech adoption for business processes by small businesses largely remains unexplored in the context of emerging markets. This study was conducted during late 2018 using a sample of 117 owner and managers of small businesses in India, for exploring the fintech adoption through the Technology Organization Environment (TOE) framework. The method applied for data analysis was partial least squares s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…MSMEs need information solutions and implementation that are in accordance with their size and needs in improving their performance to have high competitiveness (Issa, Lucke and Bauernhansl, 2017). According to Varma (2019), adopting financial technology is a financial solution carried out by technology such as the use of digital payments, mobile banking, internet banking, and others. Research conducted by Varma (2019) stated significant relevance for understanding the adoption of financial technology in MSMEs, especially in developing countries like India.…”
Section: Financial Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…MSMEs need information solutions and implementation that are in accordance with their size and needs in improving their performance to have high competitiveness (Issa, Lucke and Bauernhansl, 2017). According to Varma (2019), adopting financial technology is a financial solution carried out by technology such as the use of digital payments, mobile banking, internet banking, and others. Research conducted by Varma (2019) stated significant relevance for understanding the adoption of financial technology in MSMEs, especially in developing countries like India.…”
Section: Financial Technologymentioning
confidence: 99%
“…Research conducted by Varma (2019) stated significant relevance for understanding the adoption of financial technology in MSMEs, especially in developing countries like India. Research conducted by Varma (2019) found that aspects of technology-organization-environment (TOE) are related to the adoption of financial technology. The results of the study revealed that perceived direct benefits have a positive and significant impact on the adoption of MSME financial technology in India.…”
Section: Financial Technologymentioning
confidence: 99%
“…Varma 37) 2019 Fintech SME Perceived benefit is one of the determinants of the fintech adoption of Indian SMEs. Cost is not a determinant factor for fintech adoption.…”
Section: Individualmentioning
confidence: 99%
“…Data quality and integration, top management support, competitive pressure, and technology competence influence the adoption of CRM. Varma 37 identified that the benefits of Fintech significantly affected fintech adoption. Xieet al, 60) explored how individuals and organizations considered monetary costs when adopting recent technology.…”
Section: Disruptive Innovationsmentioning
confidence: 99%
“…This second component is associated with the economy, that is, it is dedicated to examining the economic aspects and the statistical and management processes that allow an organisation to obtain economic and operational improvements. It includes terms such as cost-benefit analysis, capital financing and capital expenditures [126,127]. Cluster 3 is made up of 16.56% of the keywords and is headed by "Technology Transfer" (occurrences: 124, total link strength: 885).…”
Section: Analysis Of Abstractmentioning
confidence: 99%